2021
DOI: 10.3389/fphys.2021.715417
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Body EMS Superimposed Walking and Nordic Walking on a Treadmill—Determination of Exercise Intensity to Conventional Exercise

Abstract: Electrical muscle stimulation (EMS) is an increasingly popular training method and has become the focus of research in recent years. New EMS devices offer a wide range of mobile applications for whole-body EMS (WB-EMS) training, e.g., the intensification of dynamic low-intensity endurance exercises through WB-EMS. The present study aimed to determine the differences in exercise intensity between WB-EMS-superimposed and conventional walking (EMS-CW), and CON and WB-EMS-superimposed Nordic walking (WB-EMS-NW) du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 35 publications
0
6
1
Order By: Relevance
“…On the other hand, Verch et al [38] aimed to determine the differences in VO 2 comparing Nordic walking and walking with and without WB-EMS. They continuously applied WB-EMS during 10 min with the following pattern: 9 s at 85 Hz and 1 s at 7 Hz, with a pulse width 350 µsec in every muscle stimulated at the individual tolerated maximum intensity [38]. Interestingly, they found a ≈ 10% increase in VO 2 elicited by WB-EMS [38].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, Verch et al [38] aimed to determine the differences in VO 2 comparing Nordic walking and walking with and without WB-EMS. They continuously applied WB-EMS during 10 min with the following pattern: 9 s at 85 Hz and 1 s at 7 Hz, with a pulse width 350 µsec in every muscle stimulated at the individual tolerated maximum intensity [38]. Interestingly, they found a ≈ 10% increase in VO 2 elicited by WB-EMS [38].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Kemmler et al [32] applied high frequencies (i.e., 80-85 Hz) at the subject's maximum tolerance levels. Similarly, Verch et al [38] applied 85 Hz WB-EMS during 10 min of walking and Nordic walking finding an ≈10% increase in EE.…”
Section: Introductionmentioning
confidence: 90%
“…The descriptive statistics generated by the total of the sample (Table 1) revealed that the profile of the WB-EMS user is a middle-aged woman (35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49), with normal weight, active (59% do another type of physical activity apart from WB-EMS training) with university studies, who seeks one of the following three goals: weight loss, increasing muscle mass or improving health and wellness. On the other hand, we can also profile the male user, it is a little younger (33% vs. 27.6% between 18-34 years), also with university studies (85%) and more active than women's (76.2% vs. 59.8% p < 0.05 from pairwise z-test).…”
Section: Resultsmentioning
confidence: 99%
“…There are studies conducted with 1 weekly session [30][31][32], 1.5 (3 session in two weeks) [12,33] and 2 times a week sessions [34,35]. The positive effects demonstrated by WB-EMS range from rehabilitation and pain relief [26,36,37], change in body composition [21,[38][39][40], increase in muscle mass [41,42], strength [22,25,43] and endurance [44][45][46].…”
Section: Introductionmentioning
confidence: 99%
“…Effects were observed after just one training session [ 11 , 12 ], ranging up to several weeks of training [ 6 , 10 , 14 ]. In contrast, only few studies have investigated the application of wbEMS to enhance endurance performance [ 6 , 14 , 15 ]. In a previous study with isolated EMS, Paillard and colleagues [ 4 ] found that EMS places a high demand on muscle metabolism and can increase energy consumption and carbohydrate oxidation more effectively than voluntary contraction.…”
Section: Introductionmentioning
confidence: 99%